2007
DOI: 10.1088/1367-2630/9/8/249
|View full text |Cite
|
Sign up to set email alerts
|

Possible evidence of non-Fermi liquid behaviour from Quasi-one-dimensional indium nanowires

Abstract: We report possible evidence of non-Fermi liquid (NFL) observed at room temperature from the quasi one-dimensional (1D) indium (In) nanowires self-assembled on Si(111)-7×7 surface. Using high-resolution electron-energy-loss spectroscopy, we have measured energy and width dispersions of a low energy intrasubband plasmon excitation in the In nanowires.We observe the energy-momentum dispersion ω(q) in the low q limit exactly as predicted by both NFL theory and the random-phase-approximation. The unusual non-analyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…(Here, λ is the propagation wavelength of the plasmonic charge-density wave in the wire.) This was also observed in previous momentum-resolved EELS experiments [79,82,86]. For a finite wire with length L, plasmonic excitation with wavelength λ longer than 2L is not possible and the plasmon frequency remain the same as that for λ = 2L = 2π/q ; it forms a standing wave, enabling optical detection.…”
Section: Future Perspectives: Standing-wave Localized Plasmons In An supporting
confidence: 76%
See 1 more Smart Citation
“…(Here, λ is the propagation wavelength of the plasmonic charge-density wave in the wire.) This was also observed in previous momentum-resolved EELS experiments [79,82,86]. For a finite wire with length L, plasmonic excitation with wavelength λ longer than 2L is not possible and the plasmon frequency remain the same as that for λ = 2L = 2π/q ; it forms a standing wave, enabling optical detection.…”
Section: Future Perspectives: Standing-wave Localized Plasmons In An supporting
confidence: 76%
“…The observed feature is associated with low-energy plasmonic excitation in atomic wires [16,46,47,79,80,86]. For sufficiently long indium wires, the plasmon frequency undergoes a redshift as the plasmon wavelength λ increases or the plasmon momentum parallel to the wire axis q = π/λ decreases.…”
Section: Future Perspectives: Standing-wave Localized Plasmons In An mentioning
confidence: 99%
“…͑c͒ Corresponding change on the shoulder of Au 4f 7/2 peak. electron energy-loss spectroscopy study 15,33 as well as theoretical calculations 25 have shown the presence of a 1D plasmon excitation from this system with an excitation energy ranging from 0.8 to 1.0 eV, the satellite peak of the Au 4f 7/2 may reflect the plasmon excitation in the Au-Si metallic chains. This assignment becomes more plausible when one finds the remarkably weakened satellite when the surface becomes less metallic by contamination.…”
mentioning
confidence: 81%
“…8,9 The Peierls instabilities characteristic of 1D metallic system has also been invoked to this 1D metallic system. 5,6,10,24,33 Ahn et al 10 reported, however, that only S1 is metallic at room temperature ͑RT͒, which undergoes a Peierls-type metal-insulator transition ͑MIT͒ with a transition temperature T c = 120 K while S2 appears to be nonmetallic with an energy gap of about 100 meV nearly independent of T. They also observed period doubling below T c for the step-edge Si atoms associated with the S1 band in their scanning tunneling microscope ͑STM͒ images. Meanwhile from their DFT calculations, Sánchez-Portal et al 9,18 showed that the splitting of a surface band into two S1 and S2 bands near E F stems from the spin-orbit coupling of the Si-Au band.…”
mentioning
confidence: 99%
“…The past studies on the preparation of indium nanowires using thermal evaporation have revealed the interesting structural and electrical and optical properties of these samples [ 15 , 18 , 23 ]. Galvanic displacement or the so-called immersion plating is another way to synthesize nanoscale materials in recent years [ 24 ].…”
Section: Introductionmentioning
confidence: 99%